Effect of energy intake on performance and carcass composition of broiler chickens from two different genetic groups - Rosa, P. S. [UNESP]; Faria Filho, D. E.; Dahlke, F.; Vieira, B. S. [UNESP]; Macari, Marcos [UNESP]; Furlan, Renato Luis [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2007)
In order to evaluate the effect of energy intake and broiler genotype on performance, carcass yield, and fat deposition, 600 one-day-old male chicks from two different genetic groups (AgRoss 308 - commercial line and PCLC - Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA) non-improved line) were fed diets with different metabolizable energy level (2950, 3200 and 3450 kcal/kg). A completely randomized experimental design in a 2X3 factorial arrangement with four replications of 25 birds per treatment was applied. In order to ensure different energy intake among treatments within each strain, feed intake was daily adjusted by pair-feeding schemes. AgRoss 308 broilers had better performance and carcass yield, and presented lower abdominal fat deposition rate. In both genetic groups, the highest dietary energy level increased weight gain, heart relative weight, and fat deposition. However, it reduced the difference between AgRoss 308 and PCLC for feed conversion ratio and carcass protein deposition. These findings allow concluding that genetic improvement had a significant effect on broiler energy metabolism, and that the highest performance differences between genetic groups are found when low-energy intake is imposed.
Keywords: Allometric growth; Broiler chickens; carcass composition; energy intake; genetic strains